(untitled) (Global Journal of Medical Research, 2016)
Hepatitis B virus (HBV) has been identified by WHO as one of the deadliest viral diseases in Africa due to its high prevalence and complications. Thus urgent research and policy attention is needed to stem its spread. The study assessed factors associated with the completion of hepatitis B vaccine among Babcock University students, Nigeria. Multistage sampling procedure was employed to select 360 students to participate in the study after completing all requirements for ethical clearance. Data gathered from the respondents were subjected to descriptive analysis using the Statistical Package for Social Sciences (SPSS Ver. 17). Most of the respondents are adults above 20 years and were aware of the HBV (89%). Despite serious efforts made by the University at educating the students about Hepatitis B, more than 40 % of the students still do not know the causative organism and are totally oblivious of the importance of vaccination. Also, 73% of the students had not completed the recommended 3 dosage vaccines. The findings also showed that despite the high level of awareness up to 44 percent of the students were not sure of their status or have not been previously immunized, indicating that their knowledge did not motivate their actions or practice.